Inheritance rights of children from sirri marriages: An analysis based on fiqh and positive law in Indonesia - Nur Anshari (International Journal of Sharia Studies, 2023)
Sirri marriage or marriage under the hand is a marriage that is kept secret and not registered and not recorded based on applicable regulations. The validity of marriage under sirri according to fiqh and positive law conflicts with opinion. This article reviews these provisions based on the views of the scholars of the madhab (fiqh) and the provisions of positive law based on Law Number 1 of 1974 concerning marriage and its derivative regulations, as well as the Compilation of Islamic Law. According to fiqh law, marriage is still valid as long as it fulfils the pillars and conditions of marriage according to Islamic law. Meanwhile, according to positive law, the sirri marriage is not recognized. It will have adverse effects on children born, namely not getting legal protection for children’s rights, including the right to inheritance from their biological father and mother. However, when viewed through the lens of fiqh law, children who are born are considered to still get their rights from their father and mother, including being able to inherit property from both parents.